Two small-molecule inhibitors of Toxoplasma gondii proliferation in vitro - Hua, Qian-qian; Lin, Xue-jing; Xiang, Shi-peng; Jiang, Li-ya; Cai, Jin-hao; Sun, Jian-min; Tan, Feng; Mou, Ya-ni (Frontiers in Cellular and Infection Microbiology, 2023)
Background Toxoplasmosis caused by Toxoplasma gondii is a globally distributed zoonosis. Most infections appear asymptomatic in immunocompetent individuals, but toxoplasmosis can be fatal in fetuses and immunocompromised adults. There is an urgent need to research and develop effective and low-toxicity anti-T. gondii drugs because of some defects in current clinical anti-T. gondii drugs, such as limited efficacy, serious side effects and drug resistance. Methods In this study, 152 autophagy related compounds were evaluated as anti-T. gondii drugs. The activity of β-galactosidase assay based on luminescence was used to determine the inhibitory effect on parasite growth. At the same time, MTS assay was used to further detect the effects of compounds with over 60% inhibition rate on host cell viability. The invasion, intracellular proliferation, egress and gliding abilities of T. gondii were tested to assess the inhibitory effect of the chosen drugs on the distinct steps of the T. gondii lysis cycle. Results The results showed that a total of 38 compounds inhibited parasite growth by more than 60%. After excluding the compounds affecting host cell activity, CGI-1746 and JH-II-127 were considered for drug reuse and further characterized. Both CGI-1746 and JH-II-127 inhibited tachyzoite growth by 60%, with IC50 values of 14.58 ± 1.52 and 5.88 ± 0.23 μM, respectively. TD50 values were 154.20 ± 20.15 and 76.39 ± 14.32 μM, respectively. Further research found that these two compounds significantly inhibited the intracellular proliferation of tachyzoites. Summarize the results, we demonstrated that CGI-1746 inhibited the invasion, egress and especially the gliding abilities of parasites, which is essential for the successful invasion of host cells, while JH-II-127 did not affect the invasion and gliding ability, but seriously damaged the morphology of mitochondria which may be related to the damage of mitochondrial electron transport chain. Discussion Taken together, these findings suggest that both CGI-1746 and JH-II-127 could be potentially repurposed as anti-T. gondii drugs, lays the groundwork for future therapeutic strategies.